Mentoring unemployed science graduates in South Africa: early lessons learnt - Geber, Hilary; Koyana, Siphokazi (Acta Academica: Critical views on society, culture and politics, 2012)
As part of the National Youth Service Volunteers Programme, the Department of Science and Technology implemented the first two-year programme in 2008-2009. Unemployed science graduates were selected to participate. One hundred interns were placed in 22 science centres where they learnt work-related skills while seeking permanent jobs. As all the candidates, aged between 21 and 35, were historically disadvantaged individuals who had graduated from historically black higher education institutions, a mentoring system was implemented to help accelerate their development. This article reports on the experiences of the interns and their mentors and highlights mentoring good practice for such innovative programmes. It also contains some longitudinal data about their employment after the internship ended.